Preseptal and Orbital Cellulitis: Analysis of Clinical, Laboratory and Imaging Findings of 123 Pediatric Cases From Turkey. Issue 2 (February 2022) - Bülbül, Lida; Özkul Sağlam, Neslihan; Kara Elitok, Gizem; Mine Yazici, Zahide; Hatipoglu, Nevin; Hatipoğlu, Sami; Bakirtas Palabiyik, Figen; Yigit, Ulviye; Demir, Mesut; Bülbül, Ali
Abstract : Background: We aimed to compare the clinical and laboratory characteristics and imaging methods of patients diagnosed with preseptal cellulitis and orbital cellulitis in the pediatric age group. Methods: The study was designed retrospectively, and the medical records of all patients who were hospitalized with the diagnosis of preseptal cellulitis and orbital cellulitis were reviewed. The findings of preseptal cellulitis and orbital cellulitis groups were compared. The risk factors for the development of orbital involvement were analyzed. Results: A total of 123 patients were included, 90.2% with preseptal cellulitis and 9.8% with cellulitis. The male gender ratio was 60.2%, and the mean age was 72 ± 43 months. While all patients had eyelid swelling and redness, 20.3% had fever. Ocular involvement was 51.2% in the right eye and 4.9% in both eyes. The most common predisposing factor was rhinosinusitis (56.1%). Radiologic imaging (computed tomography/magnetic resonance imaging) was performed in 83.7% of the patients. Subperiostal abscess was detected in 7 cases (5.6%) in which three of the cases were managed surgically and four were treated with medically. The levels of C-reactive protein were significantly higher in patients with orbital involvement ( P = 0.033), but there was no difference between the presence of fever, leukocyte and platelet values. Conclusions: Rhinosinusitis was the most common predisposing factor in the development of preseptal cellulitis and orbital cellulitis. Orbital involvement was present in 9.8% of the patients. It was determined that high C-reactive protein value could be used to predict orbital involvement.